Analysis of the Quality of Service of the Population and Civil Registration Service Website of Banyuasin Regency Using the E-Govqual Method - Dayu Anggara; Evi Yulianingsih (Journal La Multiapp, 2026)
The implementation of information technology by government agencies, particularly through e-government services, has become a necessity to improve the quality of public services. The Population and Civil Registration Office of Banyuasin Regency has provided a website as a digital platform to facilitate various population administration services. The effectiveness and user satisfaction of this website need to be evaluated to determine whether the service quality is optimal. This study aims to evaluate the quality of website services using the E-GovQual method, which measures the dimensions of efficiency, reliability, trust, and user support. Data were obtained through a questionnaire completed by 273 respondents from the Banyuasin Regency community. The results are expected to provide an overview of user satisfaction levels and identify dimensions that require improvement.